Assessing youth development in Sub-Saharan Africa with a multidimensional index - Uchenna Efobi; Emmanuel Orkoh (Kiel Institute for the World Economy (IfW), Poverty Reduction, Equity and Growth Network (PEGNet), 2017)
The youth population (aged 15-24) in sub-Saharan Africa (SSA) is growing rapidly to the extent that in 2015, 226 million youths were estimated to be living on the continent. Youths in Africa currently account for 19 per cent of the global youth population. It is further projected that by 2030, Africa's youth population will increase by 42 per cent, and by 2055 it will more than double (United Nations, 2015). This rapid growth of the population is expected to limit the economic opportunities available for youths in Africa. This could further result in negative socioeconomic consequences such as the reduced contribution of youths to national economic progress, economic exclusion, and an increase in anti-social activities such as crime, rebel activities and armed conflict. [...]
Keywords: 330